Researching Self-Assessment's Impact on Speaking Skills Development in 7th-Grade Pre-A1 English Level Students - Camacho Velez, Ana Belén (2024)
One of the most widely spoken languages in the world is English, which is the most common way to communicate; as stated by Mastin (2011), “English is the nearest thing there has ever been to a global language.” (p. 2). English is very important for work, and it also makes it possible to communicate with people of different backgrounds and customs. It is important to remember that speaking skills are essential to language acquisition since language learners frequently come across new vocabulary. This presents a problem, especially for those for whom English is not their native tongue. This educational institution in Portoviejo has a problem with students who have low competency levels when developing speaking skills. This problem is related to the absence of techniques for improving oral communication in this group of students. The lack of specialized methods and resources makes it harder for students to improve their speaking abilities, which impedes their capacity to advance in their foreign language learning process. As such, students find it difficult to explain themselves in English. One of the main challenges is vocabulary, which makes people reluctant to talk since they have trouble pronouncing certain words. Their confidence and willingness to speak are impacted by this language barrier. Furthermore, there is a lack of knowledge about the syntax needed to create well-constructed sentences.